Klinične smernice za rehabilitacijo bolnikov z artrozo kolka in kolena - Pertot, Anja (Rehabilitacija (Ljubljana), 2014)
Osteoarthritis (OA) of the hip and osteoarthritis of the knee are one of the most common chronic diseases. In elderly people, OA is the most common cause of disability, including pain and limitations of activities and participation. The exact cause of OA is unknown, but there are a number of known risk factors. There were a number of recommendations published in past decade, but the two most recent are from 2012 from The European League against Rheumatism and American College of Rheumatology. These recommendations include non-pharmacological and pharmacological recommendations for the treatment of OA.
Keywords: artroza; Guidelines as Topic; Hip; klinične smernice; Knee; kolčni sklep; koleno; Osteoarthritis; rehabilitacija; vocational rehabilitation